SISTEM INFORMASI GEOGRAFIS MENENTUKAN RUTE TERDEKAT PADA FASILITAS UMUM KOTA MEDAN MENGGUNAKAN A STAR - Ratna Wildayani; Triase (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The development of Geographic Information Systems (GIS) has produced various commercial mapping applications, such as Google Maps, but these applications do not specifically provide structured mapping of public facilities with route calculations tailored to the conditions of the Medan City area. The problem faced is the lack of a GIS system that utilizes a specific dataset for public facilities in Medan City and is capable of calculating the shortest route optimally based on heuristics. This study aims to design and build a web-based geographic information system that determines the shortest route to public facilities in Medan City using the A Star algorithm with local public facility coordinate data. The uniqueness of this study lies in the use of a specific dataset for public facilities in Medan City and the application of distance heuristics based on latitude-longitude conversion to kilometers for an urban context. The results show that the system successfully found the shortest route with a total distance of 7.65 km, which is more optimal than direct Euclidean distance calculations without graph optimization. This system provides a more efficient and targeted route, thereby increasing public access to public facilities in Medan City.